Adoption of Big Data Analytics in Indonesian Public Sector Auditing - Rahayu Alkam; Achdian Anggreny Bangsawan; Indri Iswardhani (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aimed to examine the adoption of big data analytics (BDA) in public sector auditing in Indonesia, based on empirical data collected in 2022. The growing use of digital technologies in audit processes is expected to improve effectiveness and efficiency; however, their implementation also demands considerable financial and organizational resources. Thus, it is important to explore both the benefits and challenges of BDA adoption in the public sector context. Research Method: Data were collected through in-depth semi-structured interviews with eight auditors from IT and non-IT backgrounds. A qualitative approach was used to analyze the data, supported by a big data governance framework. Results and Discussion: The findings indicate that BDA adoption in Indonesian public-sector auditing remains at an early stage. Although BDA offers opportunities such as improved red-flag detection, full-population analysis, and enhanced audit effectiveness and efficiency, several challenges remain, including platform stability, data accessibility, and human resource readiness. Implications: This study provides empirical evidence on the processes, opportunities, and challenges of BDA utilization from the perspective of public-sector auditors. Future studies should examine further developments in BDA use in Indonesian public institutions and offer new perspectives through different participants or methods. BPK is expected to prioritize human resource readiness and platform development. Originality: This study contributes to the limited empirical research on BDA utilization in public sector auditing by presenting insights from auditors’ perspectives.